Regionalne zróżnicowanie możliwości inwestycyjnych jednostek samorządu terytorialnego w Polsce - Markowska-Bzducha, Ewa (The Regional Differentiation of the Possibility of Investment - Local Government Units in Poland, 2007)
The incorporation of Poland into the European Union in 2004 has given this country the opportunity of using the EU's relief funds - over 12 billion euro allocated for the years 2004-2006. Main beneficiaries of these funds in Poland are local government units. The paper presents an analysis of changes in incomes of local government units in Poland in view of increasing their opportunities in using the EU's relief funds. The analysis was based on incomes of Polish regions in the years 2002-2004.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 509-519